COVID-19 in Solid Organ Transplantation: A Matched Retrospective Cohort Study and Evaluation of Immunosuppression Management. Issue 1 (15th September 2020) - Miarons, Marta; Larrosa-García, María; García-García, Sonia; Los-Arcos, Ibai; Moreso, Francesc; Berastegui, Cristina; Castells, Lluís; Pérez-Hoyos, Santiago; Varela, Javier; Pau-Parra, Alba; Varón-Galcera, Carlota; Parramon-Teixidó, Carlos-Javier; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The epidemiological and clinical characteristics of solid organ transplant (SOT) patients during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic remains unclear. We conducted a matched retrospective cohort study to compare clinical outcomes among SOT recipients with the general population and to assess immunosuppression management. Methods: Adult SOT recipients with laboratory polymerase chain reaction–confirmed SARS-CoV-2 infection admitted to a tertiary-care hospital in Barcelona, Spain, from March 11 to April 25, 2020, were matched to controls (1:4) on the basis of sex, age, and age-adjusted Charlson's Index. Patients were followed for up to 28 days from admission or until censored. Primary endpoint was mortality at 28 days. Secondary endpoints included admission to the intensive care unit and secondary complications. Drug–drug interactions (DDI) between immunosuppressants and coronavirus disease 2019 (COVID-19) management medication were collected. Results: Forty-six transplant recipients and 166 control patients were included. Mean (SD) age of transplant recipients and controls was 62.7 (12.6) and 66.0 (12.7) years, 33 (71.7%) and 122 (73.5%) were male, and median (interquartile range) Charlson's Index was 5 (3–7) and 4 (2–7), respectively. Mortality was 37.0% in SOT recipients and 22.9% in controls ( P = 0.51). Thirty-three (71.7%) patients underwent transitory discontinuation of immunosuppressants due to potential or confirmed DDI. Conclusions: In conclusion, hospitalized SOT recipients with COVID-19 had a trend toward higher mortality compared with controls, although it was not statistically significant, and a notable propensity for DDI.